Pengaruh Rekrumen dan Seleksi terhadap Kinerja Pegawai pada Hotel Abadi Suite Kota Jambi - Ika Mulyani (Universitas Batanghari Jambi, 2022)
This study aims to determine how the effect of recruitment and selection on employee performance at the Abadi Suite Hotel Jambi City simultaneously and partially and how much influence recruitment and selection have on employee performance at the Abadi Suite Hotel Jambi City.The object of this analysis is the Hotel Abadi Suite Jambi City. The sample used in this study were 38 employees at the Abadi Suite Hotel, Jambi City. The method used is descriptive analysis method with recruitment and selection independent variables while the dependent variable is employee performance. The analytical tool used in this research is multiple linear analysis, classical assumption test consisting of normality test, multicollinearity test, heteroscedasticity test, coefficient of determination and hypothesis testing (f test and t test). Based on the calculation results of SPSS version 22, on multiple linier regression analysis, Y = 0,290+0,468X1+0,472X2+e with an R Square value of 71,6%, while the remaining 28,4% is explained by other variables outside the research model. The F test is 44,1565 and the t test is 3,464 for the Recruitment variable (X!) and 3,442 for the Selection variable (X2). The conclusion of this study shows that recruitment and selection simultaneously have a significant effect on employee performance, partially recruitment and selection have a significant effect on employee performance.